Commodity risk assessment of Prunus avium plants from United Kingdom - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2024)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects'. This Scientific Opinion covers plant health risks posed by plants of Prunus avium possibly grafted on rootstocks of either P. avium, P. canescens, P. cerasus, P. pseudocerasus or their hybrids imported from the UK, taking into account the available scientific information, including the technical information provided by the UK. All pests associated with the commodities were evaluated against specific criteria for their relevance for this opinion. Three quarantine pests Scirtothrips dorsalis, tobacco ringspot virus and tomato ringspot virus), one protected zone EU quarantine pest (Bemisia tabaci (European population), and three non‐ regulated pests (Colletotrichum aenigma, Eulecanium excrescens and Takahashia japonica) that fulfilled all relevant criteria were selected for further evaluation. The risk mitigation measures proposed in the technical Dossier from the UK were evaluated, taking into account the possible limiting factors. For these pests, expert judgement is given on the likelihood of pest freedom, taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The degree of pest freedom varies among the pests evaluated, with Colletotrichum aenigma being the pest most frequently expected on the imported potted plants. The Expert Knowledge Elicitation indicated with 95% certainty that between 9971 and 10,000 plants per 10,000 would be free from the above‐mentioned fungus.